A Survey on Cultural İdentities of Turkish Youth Living in Berlin - Şişman, B. (My University, 2005)
This study is a questionnaire. Yet, findings of surveys and interviews are used in this study. The questionnaire is used among 100 Turkish youth between 18 and 25 living in Berlin. The gender of the youth is %40 male, and %60 female. Language, education an unemloyment exist important problems for Turkish youth, though they have improved themselves in same fields. Within bilingual and bicultural society, they have managed to preserve their identities and culturel merits. The findings of the questionnaire have shown difference between university students the one obtained and citizenship of this country. Culturel change is not a process only Turkish people have experinced in Germany. Today it is the one felt in Turkey and in among countries of the world as well, as consequence of social, economic and technological developments. This process develops faster for Turkish community in Germany due to the social, economik and lawful conditions. However, people of minor communities living to gether in same places can preserve their identities, traditions and they are not much open to assimilation. On the other hund, the matter of entagration is a matter of education. Turkish people are of course expected to adapt themselves to the order of law, constitutional rules, and other conditions of the country where they invited as guest workers at the beginning.
Berlin'de Yaşayan Türk Gençlerinin Kültürel Kimlikleri Üzerine Bir Araştırma
Keywords: Berlin; Change; Cultural Identity; Questionnaire; Turkish Youth